Effect of alkyl chain length in the terminal ester group on mesomorphic properties of new chiral lactic acid derivatives. Issue 10 (8th August 2016) - Kohout, Michal; Bubnov, Alexej; Šturala, Jiří; Novotná, Vladimíra; Svoboda, Jiří
ABSTRACT: Two series of new liquid crystalline lactic acid derivatives with a terminal ester group have been synthesised. The effect of this ester unit and the length of its alkyl chain on the mesomorphic and dielectric properties of the compounds exhibiting a broad temperature range of chiral smectic phases have been studied. We found that the mesomorphic behaviour and phase transition temperatures are strongly affected by the molecular architecture. Depending on the alkyl chain length in the terminal ester unit, the studied materials exhibited paraelectric smectic A*, ferroelectric tilted smectic C* and antiferroelectric smectic CA * phases over a broad temperature range. The physical properties of the compounds have been studied by optical polarising microscopy, differential scanning calorimetry, electro-optic measurements, small-angle X-ray scattering and dielectric spectroscopy. Furthermore, the homologues with short terminal alkyl chains showed a very small layer shrinkage at the transition from the orthogonal SmA* to the tilted SmC* phase, which is a characteristic feature of 'de Vries-type' behaviour. Graphical Abstract: